1982
DOI: 10.3146/i0095-3679-9-2-12
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatographic Profile of Good Quality Raw Peanuts

Abstract: Raw Virginia peanuts were evaluated from volatiles obtained by a modified direct gas chromatographic procedure. The volatiles were eluted and absorbed onto a Tenax-MPE column which was at ambient temperatures. After the peanut sample was removed, the column was temperature programmed for the analysis. The combined peak areas of methanol, acetaldehyde, ethanol, and the acetone group (pentane, 2-propano1, propanal, and acetone) usually comprised about 80% of the total volatile peak area. Sensory data and their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…Other investigators who have identified the same compounds are cited in Table 1. Methyl formate, 2-propanol and propanal have been reported by previous workers Lovegren et al, 1982;Ho et al, 1982, respectively) but were not identified in this work.…”
Section: Resultscontrasting
confidence: 63%
“…Other investigators who have identified the same compounds are cited in Table 1. Methyl formate, 2-propanol and propanal have been reported by previous workers Lovegren et al, 1982;Ho et al, 1982, respectively) but were not identified in this work.…”
Section: Resultscontrasting
confidence: 63%
“…Reduction of green, beany flavor in soybean milk has been partially accomplished by hot water extraction (Wilkens et al, 1967) and treatment with proteolytic enzymes (Fujimaki et al, 1971), aldehyde dehydrogenase (Chiba et al, 1979) and aldehyde oxidase (Takahashi et al, 1979) raw peanuts and peanut milk are similar to those present in soybeans and soybean milk. These include methanol, acetaldehyde, ethanol, pentane, acetone, pentanal and hexanal (Pattee et al, 1969;Lovegren et al, 1982). Bourne et al (1976) reported that there was a traditional belief among consumers that the use of a mild alkali such as NaHCOS improves eating quality of cooked common dIy beans.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile components of raw peanuts have been attributed to the action of lipoxygenase (Brown et al, 1977;Pattee et al, 1969 , 1976). Methanol, acetaldehyde, ethanol, pentane, acetone, pentanal and hexanal constituted most of the volatiles in published reports (Pattee et al, 1969;Lovegren et al, 1982).…”
Section: Headspace Volatilesmentioning
confidence: 96%